2021
DOI: 10.3390/f12081053
|View full text |Cite
|
Sign up to set email alerts
|

Radial Growth Response of Scots Pine (Pinus sylvestris L.) after Increasing the Availability of Water Resources

Abstract: In the years 1998–2022, about eight thousand hydrotechnical facilities were built or planned for construction at the State Forests National Forest Holding in Poland, which could slow down the outflow of water from small forest catchments and store over 50 hm³ of water. Due to the innovative and unprecedented nature of investments retaining water resources on forest land, having a significant impact on the adaptation and mitigation of the negative effects of climate change, the literature on the subject lacks i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Previous research has identified tree growth response to reservoir impoundment or lake with fluctuating water levels resembling a reservoir. Some studies applied tree-ring width to detect radial growth and plant phenology responding to changes in precipitation, temperature, and drought induced by reservoir impoundment [33][34][35]. Through a spatial comparison between coastal and inland trees in the vicinity of aquatic lakes, the response patterns of radial growth were found to be similar to those seen in reservoir impoundment [36].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has identified tree growth response to reservoir impoundment or lake with fluctuating water levels resembling a reservoir. Some studies applied tree-ring width to detect radial growth and plant phenology responding to changes in precipitation, temperature, and drought induced by reservoir impoundment [33][34][35]. Through a spatial comparison between coastal and inland trees in the vicinity of aquatic lakes, the response patterns of radial growth were found to be similar to those seen in reservoir impoundment [36].…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal and annual fluctuations in precipitation and temperature are the most common factors limiting the growth of sensitive trees [8]. Many researchers have found a dependence between changes in the radial growth of woody plants and climatic factors, in particular, temperature and soil moisture [9][10][11][12]. However, as noted by the researchers themselves, the correlation between the growth characteristics of woody plants and the values of meteorological and hydrodynamic variables are currently not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…This study also aims to determine whether there is a regularity of the change in the temperature factor by the value of the annual radial increment of the different species of trees used in landscaping an industrial city. It should be noted that there are essentially no studies on the influence of the creation of artificial reservoirs on the radial growth of woody plants [12]. At the same time, thanks to such studies, it is possible to track the real physiological change in plants in response to such a coordinate in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Scots pine (Pinus sylvestris L.) is a species in the Pinaceae family and is the main forest-forming species in Eurasia which, due to a high ecological and economic importance, attracts much interest of foresters and naturalists [1,2]. Both the needles and the bark of Scots pine can be used medicinally.…”
Section: Introductionmentioning
confidence: 99%